2010
DOI: 10.1155/2010/642804
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the Use of Artificial Chromosomes and Minichromosome-Like Episomes in Gene Therapy

Abstract: Artificial chromosomes and minichromosome-like episomes are large DNA molecules capable of containing whole genomic loci, and be maintained as nonintegrating, replicating molecules in proliferating human somatic cells. Authentic human artificial chromosomes are very difficult to engineer because of the difficulties associated with centromere structure, so they are not widely used for gene-therapy applications. However, OriP/EBNA1-based episomes, which they lack true centromeres, can be maintained stably in div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 193 publications
(196 reference statements)
0
7
0
Order By: Relevance
“…Human artificial chromosomes combine unique properties for transgenic (1) and putative gene therapeutic (2) applications and are essential to study the function and architecture of chromosome structural elements (3–6)—mainly centromeres and telomeres.…”
Section: Introductionmentioning
confidence: 99%
“…Human artificial chromosomes combine unique properties for transgenic (1) and putative gene therapeutic (2) applications and are essential to study the function and architecture of chromosome structural elements (3–6)—mainly centromeres and telomeres.…”
Section: Introductionmentioning
confidence: 99%
“…It thus seems that an optimal gene therapy approach for FRDA should guarantee physiologically-regulated expression of the frataxin gene. Indeed, the use of large DNA molecules containing whole genomic loci has recently received attention as an emerging alternative to the use of cDNAs within viral vectors for gene therapy [18,31]. Studies performed in transgenic mice have demonstrated the benefits of using large fragments of genomic DNA, which allow the delivery of intact mammalian genes with all their regulatory elements.…”
Section: Hsv-1 Vector Harboring Frataxin Genomic Locus (Ibac-fxn)mentioning
confidence: 99%
“…Amplicon vectors based on herpes simplex virus 1 (HSV-1) are one of the most promising alternatives for the delivery of large DNA molecules in gene therapy protocols as they can accommodate DNA molecules as big as 150 kb [14,31]. This makes them ideal vehicles for delivering entire genomic loci with all their regulatory elements [41,42].…”
Section: Hsv-1 Vector Harboring Frataxin Genomic Locus (Ibac-fxn)mentioning
confidence: 99%
“…To achieve this, they must contain the minimal elements required for chromosome function, namely an origin of replication, telomeres and centromeres (Pérez-Luz & Díaz-Nido, 2010). One approach towards constructing HACs, called "top-down", involves fragmentation of already existing chromosomes and generation of smaller mini-chromosomes, where only the three functional chromosomal elements remain.…”
Section: Human Artificial Chromosomesmentioning
confidence: 99%
“…The elements responsible for controlled and tissue-specific expression of a gene usually lie within the introns and the sequences before and after the gene. Therefore, the use of genomic constructs which contain the introns and flanking DNA of the therapeutic gene is expected to be more effective than that of minigene constructs in gene therapy for certain genetic diseases where precise levels of the gene product are required (reviewed by (Pérez-Luz & Díaz-Nido, 2010)). Bacterial Artificial Chromosomes (BACs), originating from the human genome project, contain genomic loci of approximately 180 kb on average and cover the entire human genome (Osoegawa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%